2022
DOI: 10.1073/pnas.2116632119
|View full text |Cite
|
Sign up to set email alerts
|

Why marginal CO2emissions are not decreasing for US electricity: Estimates and implications for climate policy

Abstract: Marginal emissions of CO2 from the electricity sector are critical for evaluating climate policies that rely on shifts in electricity demand or supply. This paper provides estimates of marginal CO2 emissions from US electricity generation using the most recently available and comprehensive data. The estimates vary by region, hour of the day, and year to year over the last decade. We identify an important and somewhat counterintuitive finding: While average emissions have decreased substantially over the last d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 45 publications
3
44
2
Order By: Relevance
“…10 and 11). Though average emissions have been decreasing, marginal emissions have been increasing in the United States over the past decade 64 . The control used average emissions as a fixed objective throughout the year.…”
Section: Grid Emissionsmentioning
confidence: 99%
“…10 and 11). Though average emissions have been decreasing, marginal emissions have been increasing in the United States over the past decade 64 . The control used average emissions as a fixed objective throughout the year.…”
Section: Grid Emissionsmentioning
confidence: 99%
“…29 Thus, a high round trip efficiency for recovering and reusing the braking energy of about 85% permits drastically reducing the net energy required to cover the cycle by 1 /4. Thus, the transition from MVs to HEVs and PHEVs has a huge immediate advantage of reducing the energy requirement by 1 Figure 2B presents the scheme of a much simpler series hybrid HC ICE/lithium-ion batteries propulsion system for a passenger car. In this case, the evolution of a BEV is pursued through the addition of a range extender engine, a high-efficiency small ICE is continuously operated at a constant speed and load as soon as the SOC of the battery falls below a threshold to recharge the battery.…”
Section: Suggested Improvements Of Phevs and Fcvs Toward 2030mentioning
confidence: 99%
“…Holland et al 1 recently analyzed the Biden administration's target of having battery electric vehicles (BEVs) making up 50% of new vehicle purchases by 2030. They found more than half the emission reductions from having fewer gasoline-powered vehicles, without significant changes to the electricity sector, are offset by the increase in electricity emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that AEFs would seriously erroneously calculate the emissions related to the intervention. Some studies pointed out that AEFs had around 20–50% errors due to the difference in the end-use of electricity and the level of emission reduction. ,, Opposite trends have been found in the U.S. electricity AEFs and MEFs due to the increased dependence on coal for marginal electricity demand . Therefore, MEFs were usually used to calculate the carbon emission impact of energy storage systems.…”
Section: Introductionmentioning
confidence: 99%
“…14,18,19 Opposite trends have been found in the U.S. electricity AEFs and MEFs due to the increased dependence on coal for marginal electricity demand. 20 Therefore, MEFs were usually used to calculate the carbon emission impact of energy storage systems. The existing short-run MEF calculation methods were mainly divided into economic dispatch models and comprehensive statistical models.…”
Section: Introductionmentioning
confidence: 99%